Addressing delays in medication administration for patients transferred from the hospital to the nursing home: A pilot quality improvement project. - Ward KT; Bates-Jensen B; Eslami MS; Whiteman E; Dattoma L; Friedman JL; Decastro Mariano J; Moore AA (American Journal of Geriatric Pharmacotherapy, 2008)
Background: Patients being transferred to a nursing home (NH) after an acute hospitalization are subject to adverse effects, including medication errors, related to poor coordination of care across settings. Objective: The goal of this study was to develop, implement, and evaluate the impact of a pilot intervention to improve patient safety by reducing delays in administration and omission of medications among patients discharged from the hospital to the NH. Methods: An expedited discharge protocol was developed in collaboration with hospital physician residents, hospital discharge planners, and NH staff (administrators, directors of nursing services, and licensed nurses). The intervention included education of the involved health care professionals and implementation of the expedited protocol to ensure that medication orders were transmitted to the NH-contracted pharmacy before patients' arrival at the NH. The intervention protocol was compared with a standard discharge protocol among patients aged >/=65 years being discharged from 2 university-affiliated hospitals to a single proprietary NH. The primary outcomes were the time between arrival at the NH and administration of first dose of an ordered medication; the number of omitted medications; the proportion of patients experiencing medication omissions; and the proportion of patients with omitted medications that had a low, medium, and high potential for negative consequences. Results: The study involved 10 patients discharged from each of the 2 hospitals and transferred to the NH. Although several components of the intervention were successfully implemented, none of the medication orders were transmitted to the NH-ccontracted pharmacy before patients' arrival at the NH. All 17 patients with medications ordered to be administered in the evening had >/=1 dose of a medication omitted after their arrival at the NH. The mean (SD) delay from arrival at the NH to administration of the first dose of an ordered medication was 12.55 (7.45) hours. The mean number of doses of different medications omitted per patient was 3.4 (2.60). Sixty-seven doses of medications were omitted; 53 of these omissions involved only 1 dose of a medication. Thirty-three percent of omitted doses involved medications with the highest potential for resulting in a negative consequence. Conclusions: The intervention to improve patient safety by reducing medication delays for patients making the transition from the hospital to the NH was not successfully implemented, as medication orders were not transmitted to the NH-contracted pharmacies before patients' arrival at the NH. All patients making the transition from hospital to NH experienced a >12-hour delay in medication administration, and the mean number of missed doses of medications was >3. There is a need for further exploration of the reasons for and possible solutions to delays in medication administration during the transition to the NH, as well as of the impact of such delays on patient outcomes, including adverse drug events, emergency department visits, and rehospitalizations.